Peningkatan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu Menggunakan Model Pembelajaran Kooperatif Tipe NHT Kelas IV Sekolah Dasar - Putri, Yolanda Dwi; Desyandri, Desyandri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This study aims to describe an increase in student learning outcomes in integrated thematic learning using cooperative learning type IV grade type elementary school learning model. The type of research is PTK using qualitative and quantitative approaches. The research subjects were teachers and 27 students. The results showed an increase. In the first cycle, the RPP observation results from 74,95% to 93% in the second cycle. The implementation of the aspects of teachers and students in the first cycle was 80,4% to 96,8% in the second cycle. Student learning outcomes 67.7 to 86.9 in cycle IIKeywords: Cooperative Learning Model NHT Type, Learning Outcomes